A Small‐Molecule Protein–Protein Interaction Inhibitor of PARP1 That Targets Its BRCT Domain1. Issue 8 (7th January 2015) - Na, Zhenkun; Peng, Bo; Ng, Shukie; Pan, Sijun; Lee, Jun‐Seok; Shen, Han‐Ming; Yao, Shao Q.
Abstract Poly(ADP‐ribose)polymerase‐1 (PARP1) is a BRCT‐containing enzyme (BRCT=BRCA1 C‐terminus) mainly involved in DNA repair and damage response and a validated target for cancer treatment. Small‐molecule inhibitors that target the PARP1 catalytic domain have been actively pursued as anticancer drugs, but are potentially problematic owing to a lack of selectivity. Compounds that are capable of disrupting protein–protein interactions of PARP1 provide an alternative by inhibiting its activities with improved selectivity profiles. Herein, by establishing a high‐throughput microplate‐based assay suitable for screening potential PPI inhibitors of the PARP1 BRCT domain, we have discovered that (±)‐gossypol, a natural product with a number of known biological activities, possesses novel PARP1 inhibitory activity both in vitro and in cancer cells and presumably acts through disruption of protein–protein interactions. As the first known cell‐permeable small‐molecule PPI inhibitor of PAPR1, we further established that (−)‐gossypol was likely the causative agent of PARP1 inhibition by promoting the formation of a 1:2 compound/PARP1 complex by reversible formation of a covalent imine linkage.